The impact of accrual earnings management on the firm's market value: Mediating role of government ownership and social responsibility disclosure - Alireza Habibi; Maryam Emamimibody (New Applied Studies in Management, Economics & Accounting, 2025)
This paper explores the role of CSR disclosure and government ownership in the effect of accrual earnings management on the company's market value. Data from 173 companies admitted to the Tehran Stock Exchange for the period 2013-2022 were used to test the hypotheses, and robustness tests were used to ensure the model estimation results and to identify the model estimation method. Based on the obtained results, research models have been estimated as a panel with fixed effects. It was determined that Accrual earnings management has had a negative and significant effect on the market value of companies listed on the Tehran Stock Exchange. The role of CSR disclosure in the effect of accrual earnings management on the company's market value has been positive and significant. Also, the role of government ownership has a positive and significant effect on the market value of the company as a result of accrual earnings management, and the simultaneous role of state ownership and CSR disclosure has a positive and significant effect on the company's market value as a result of accrual earnings management. The results of the hypotheses are in line with the representation theory and confirm the positive and meaningful role of government ownership and disclosure of social responsibility. The results of the study provide a new insight into the role of government ownership and CSR disclosure in the effect of accrual earnings management on the value of the company in the Tehran Stock Exchange market as the capital market of Iran. This paper highlights the importance of considering country-specific factors such as government ownership while analyzing market reactions to CSR disclosure and accrual earnings management.